Estudo ecofisiológico e prospecção de cianobactérias: crescimento, fotossíntese e composição bioquímica relacionados ao controle de fatores abióticos - Silva, Douglas Henrique Baracho da (2022)
The study of phytoplankton has been a growing field of investigation due to the versatility for using these organisms. This investigation focuses on Cyanobacteria, photosynthetic prokaryotic organisms, important under the aspects of ecology and biotechnology. In the biotechnological field, they can be a source of products for the food, cosmetics, nutraceuticals, textile industries, among others. However, a limited number of species are used commercially. This work aimed at studying the physiology and biochemical composition of cyanobacteria, as well as to evaluate the physiological response to abiotic control of cultivation conditions. Initially, we prospected 20 strains, evaluating growth, and biochemical composition (pigments, proteins, carbohydrates and lipids, antioxidant potential, phenolic compounds and polyhydroxyalkanoates), in addition to photosynthesis through chlorophyll fluorescence (quantum yields, photochemical quenching and rapid light curve parameters). Then, we performed biochemical manipulation of the biomass of a specific taxon, selected based on the prospecting results, Nostoc sp. The biochemical manipulation consisted of adding sodium chloride or copper, together with culture exposure to blue, red and green lights. The results showed great versatility of the cyanobacteria Nostoc sp., but also some resilience to variations in the conditions imposed on the cultures. Under ideal growing conditions Leptolyngbya sp. and Nostoc sp. reached higher growth rates (0,71 d-1), but Phormidium sp. and Microcystis sp. higher biomass yield (0,8 g L-1). Pigment composition varied among the studied species. The highest percent of proteins in the biomass were determined in Geitlerinema unigranulatum (60%), of carbohydrates in Microcystis navacekii (30%) and of lipids in Phormidium sp. (20%). Polyhydroxyalkanoate contents were higher (~ 2%) in Aphanocapsa holsatica, Sphaerocavum brasiliense, Microcystis aeruginosa and Nostoc sp. The photosynthetic parameters for the 20 species remained constant throughout the cultivation period. Regarding the manipulation process in Nostoc sp. we observed that sodium chloride and copper acted differently on the biomolecules. Sodium chloride led to increased phycobilins (at least 2x), whereas under copper increased (greater 1.2x) chlorophyll a and carotenoids were obtained. Proteins, carbohydrates and lipids per unit of biomass decreased in both chemical stimuli. Light colors did not influence these parameters but altered the production of phenolic compounds (1.4x) and antioxidant activity (2x). Blue light resulted in higher maximum quantum yields, rETRmax and Ik, but these gains were not reflected in the population growth of Nostoc sp. This study is a contribution to understanding the physiology of Cyanobacteria, as well as a contribution of new strains for biotechnological use.